Immunohistochemical analysis of beta-catenin expression: a probable prognostic marker and potential therapeutic target in renal cell carcinoma - Kundu, Ayan; Sen, Anway; Choudhury, Shouvik; Mandal, Tapan Kumar; Guha, Debasish; Lahiry, Sandeep (Medicine and Pharmacy Reports, 2021)
Background and aims. Renal cell carcinoma (RCC) seems to be the most aggressive type of genitourinary neoplasm. Down regulation of normal beta-catenin expression contributes to development of RCC, reflecting the role of beta-catenin/Wnt signaling pathway in pathogenesis. This study aims to evaluate the significance of beta-catenin expression and its correlation with the prognostic parameters. Methods. A cross-sectional observational study was carried out in a tertiary care center on 58 RCC cases using variables like histological grade and type, tumor stage, necrosis. Formalin fixed, paraffin-embedded blocks were evaluated for beta-catenin expression by immunohistochemistry using scoring system. Data were analyzed by mean ± SD, χ2 test, Pearson’s correlation test. Results. Membranous score (MS) had a strong negative correlation with tumor stage (r = -0.407, p = 0.044) and grade (r = -0.787, p = <0.001). Mean membranous score difference between low (Stage 1 and 2) vs. high stage (Stage 3 and 4) and low (Grade 1 and 2) vs. high grade (Grade 3 and 4) was statistically significant (p < 0.001). Cytoplasmic score (CS) had positive correlation with tumor stage (r = 0.586; p = 0.002). No significant correlation was evident between cytoplasmic scores and tumor grade, however the mean cytoplasmic score difference between low grade vs. high grade was statistically significant (p < 0.001). Conclusion. Beta-catenin may play a crucial role in the pathogenesis of RCC and has a positive correlation with the biological behavior of this tumor. The important role of beta-catenin as a prognostic parameter and probably a critical evaluator of targeted chemotherapy cannot be overemphasized.